European Consumer Protection : Theory and Practice. - Devenney, James; Kenny, Mel. (Cambridge : Cambridge University Press, 2012)
This topical volume provides detailed analyses of European consumer protection law in both its theoretical and practical dimensions.
6: E-consumers and effective protection: the online dispute resolution systemIntroduction; Consumers and e-consumers: mass contracting and nonexperts on the web; E- consumers and the new information requirements: widening the consumer concept; Mass-contracting and non-experts: the new rationales in e-consumer protection; Enforcing e-consumer protection beyond alternative dispute resolution (ADR): the ODR; E-confidence; The specific legal framework: the access of consumers to justice; The consumer access to justice:́ the logic of the regulatory framework for consumer ADR.
Online dispute resolution: new categories.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Law (Corporate); Consumer protection -- European Union countries; Consommateurs -- Protection -- Pays de l'Union européenne.; LAW -- Corporate; Consumer protection; European Union countries; Consumentenbescherming; Europees recht; EU-landen.